Shrimp Vannamei Culture (Litopenaeus vannamei) in Low Salinity Media on Biofloc System With Different C/N Ratio Media Intake - Scabra, Andre Rachmat; Yasa, Kadek Nuarta; Lumbessy, Salnida Yuniarti (Jurnal Media Akuakultur Indonesia, 2025)
Vannamei shrimp (Litopenaeus vannamei) is one of the superior commodity biota in the fisheries sector with one of its etyhaline abilities, namely that it can survive a wide salinity range, so it has the potential to cultivate vannamei shrimp in fresh water media. One of the cultivation systems that is currently developing is the biofloc system with the advantage of increasing the production capacity of dense biota but still being able to maintain water quality through the floc produced, apart from that it can increase biota production where the floc is able to become natural food for the biota being reared. The development of freshwater vaname shrimp cultivation using a biofloc system has never been carried out, where one of the important factors of biofloc itself is the C/N ratio for floc growth, therefore it is necessary to determine the correct C/N ratio given to the freshwater vaname shrimp biofloc media. The aim of this research is to analyze the maintenance of low salinity vaname shrimp using a biofloc system at different C/N ratios. The research method used was the experimental method with a completely randomized design (CRD) consisting of 4 treatments and 3 replications, namely P1 C/N 6, P2 C/N ratio 12, P3 C/N ratio 18, and P4 C/N ratio 18. N 24. The results of this study show a real difference in the specific weight growth rate with the highest value at P3, namely 9.0%/day and the lowest at P1, namely 0%/day. The specific length growth rate in P3 shows the highest value, namely 4.18%/day and the lowest in P1, namely 0%/day. The FCR value in the study also showed the best results at P3 with a value of 1.57.